A MODEL FOR SIMULATING WATER QUALITY IN A RIVER AND APPLICATION OF GENETIC ALGORITHM IN THE MODEL CALIBRATION - N. V. Tuan; K. Mori; Y. Hirai (International Association of Lowland Technology, 2008)
This study focuses on finding the properties of water quality parameters affected by different sources of pollutants along the Tatara River, a small river in Fukuoka city of Japan. Results getting from data analysis pointed out interesting and noticeable properties of water quality in the Tatara River, which is significantly affected by various point sources. The results also indicated the changing tendencies of water temperature and dissolved oxygen in the Tatara River in response to different meteorological conditions over a daily cycle. On the other hand, we developed and applied a numerical model to simulate the variation of water quality concentrations in the river. By calibrating the model with water quality data collected from the selected river blocks, the simulated results of dissolved oxygen and water temperature have good agreement with the observed data. In calibrating model, we used genetic algorithms that allowed users to find the best data set of parameters which could not be measured from field measurement and experiments or analyzed simply by a user. Results of the water quality model are helpful for management, protection, and improvement of the Tatara River water quality.